Down-regulation of HCP5 inhibits cell proliferation, migration, and invasion through regulating EPHA7 by competitively binding miR-101 in osteosarcoma - Tu,Yangmao (2021)
Patients with osteosarcoma (OS) usually have poor overall survival because of frequent metastasis. Long non-coding RNAs (lncRNAs) have been reported to be associated with tumorigenesis and metastasis. In this study, we investigated the expression and roles of lncRNA human histocompatibility leukocyte antigen (HLA) complex P5 (HCP5) in OS, aiming to provide a novel molecular mechanism for OS. HCP5 was up-regulated both in OS tissues and cell lines and high expression of HCP5 was associated to low survival in OS patients. Down-regulation of HCP5 inhibited cell proliferation, migration, and invasion, suggesting its carcinogenic role in OS. miR-101 was targeted by HCP5 and its expression was decreased in OS. The inhibitor of miR-101 reversed the impact of HCP5 down-regulation on cell proliferation, apoptosis, and metastasis in OS. Ephrin receptor 7 (EPHA7) was proved to be a target of miR-101 and had ability to recover the effects of miR-101 inhibitor in OS. In conclusion, lncRNA HCP5 knockdown suppressed cell proliferation, migration, and invasion, and induced apoptosis through depleting the expression of EPHA7 by binding to miR-101, providing a potential therapeutic strategy of HCP5 in OS.